Challenges, Strategies, and Impacts of Doing Citizen Science with Marginalised and Indigenous Communities: Reflections from Project Coordinators - Benyei, Petra; Skarlatidou, Artemis; Argyriou, Dimitris; Hall, Rick; Theilade, Ida; Turreira-García, Nerea; Latreche, Danielle; Albert, Alexandra; Berger, David; Cartró-Sabaté, Mar; Chang, Jessie; Chiaravalloti, Rafael; et al. (Citizen science : theory and practice, 2023)
Citizen science is growing and increasingly realizing its potential in terms of benefiting science and society. However, there are significant barriers to engaging participants in non-Western, non-educated, non-industrialised, non-rich and non-democratic contexts. By reflecting on the experiences of 15 citizen science project coordinators, this paper contributes to the small but growing body of knowledge attempting to identify barriers and opportunities of doing citizen science with marginalised and Indigenous communities. Challenges affecting participation in the analysed projects include issues that range from lack of basic infrastructure and participant safety to unbalanced knowledge hierarchies and data rights. We found that, to overcome these challenges, projects have used several strategies, from promoting decentralized and low-tech solutions to engaging in bottom-up actions from a human-rights approach. Finally, our analysis of project impacts supports the idea that doing citizen science with marginalised and Indigenous communities might have a greater impact for participants than for science, as scientific achievements (although valuable) were not among the most important impacts highlighted in terms of project success. By providing stories from the field in a structured way, we aim to guide, to inform, and to inspire other citizen science projects, and to, ultimately, contribute to broader participation in citizen science in the future.